Assembly and comparative analysis of the first complete mitochondrial genome of zicaitai (Brassica rapa var. Purpuraria): insights into its genetic architecture and evolutionary relationships - Xiao, Wanyu; Wu, Xian; Zhou, Xianyu; Zhang, Jing; Huang, Jianghua; Dai, Xiuchun; Ren, Hailong; Xu, Donglin (Frontiers in Plant Science, 2024)
Zicaitai (Brassica rapa var. purpuraria) is a Brassica variety renowned for its distinctive taste and rich nutritional profile. In recent years, the mitochondrial genomes of several Brassica species have been documented, but the mitogenome of Zicaitai remains unreported. In this study, we present the characterization of the Zicaitai mitogenome, achieved through the assembly of sequencing reads derived from both the Oxford Nanopore and Illumina platforms. A detailed comparative analysis was carried out with other Brassica species to draw comparisons and contrasts. The Zicaitai mitogenome is characterized by a circular structure spanning 219,779 base pairs, and it encompasses a total of 59 genes. This gene set includes 33 protein-coding genes, 23 tRNA genes, and 3 rRNA genes, providing a rich foundation for further genomic study. In-depth analyses of codon usage patterns, instances of RNA editing, and the prevalence of sequence repeats within the mitogenome were also conducted to gain a more nuanced understanding of its genetic architecture. An analysis of the Ka/Ks ratios for 30 protein-coding genes shared by the mitogenomes of Zicaitai and seven other Brassica species revealed that most of these genes had undergone purifying selection. Furthermore, a phylogenetic analysis was performed, utilizing the coding sequences (CDS) from the mitochondrial genome of Zicaitai and that of 20 closely related species/varieties to trace evolutionary connections. Additionally, the study explored the migration of genes between the chloroplast and nuclear genomes and the mitogenome, offering insights into the dynamics of genetic exchange within the Brassica genus. The collective results in this study will serve as a foundational resource, aiding future evolutionary studies focused on B. rapa, and contributing to a broader understanding of the complexities of plant evolution.